2023
DOI: 10.3390/healthcare11030376
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endodontic Irrigant Activation on Smear Layer Removal and Surface Disintegration of Root Canal Dentine In Vitro

Abstract: The objective of this study was to compare the ability of different endodontic irrigation activation methods to enable irrigant penetration, remove the smear layer from root canal walls after preparation, and investigate surface effects on dentine. Root canals of 90 single-rooted teeth were prepared and irrigated with EDTA (17%) and sodium hypochlorite (5%), where both irrigants or sodium hypochlorite only were activated as follows: conventional needle irrigation, ultrasonic activation, sonic activation (EDDY)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This approach is recommended in several reports [24,[80][81][82]. However, this is not in agreement with the studies showing that EDTA should be used at the end of the shaping instead of alternating EDTA and sodium hypochlorite [18,41].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This approach is recommended in several reports [24,[80][81][82]. However, this is not in agreement with the studies showing that EDTA should be used at the end of the shaping instead of alternating EDTA and sodium hypochlorite [18,41].…”
Section: Discussionmentioning
confidence: 95%
“…Different techniques may be used to enhance the action of EDTA, e.g., ultrasonic [7,36] or sonic activation [37], negative pressure irrigation [38], laser activation [39], and manual dynamic agitation [40]. At the same time, EDTA activation may also cause the surface disintegration of root canal dentin [41].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with Akbulut and Terlemez (2019), who found that root canal dentin microhardness was significantly affected by the irrigation solution, but not by the PIPS activation. Widbiller et al (2023) found that LAI activation of both NaOCl and EDTA led to pronounced surface disintegration of root canal dentine, which was higher than that of sonic (Eddy) or ultrasonic activation.…”
Section: Effect On Dentin Surface and Dentin Propertiesmentioning
confidence: 88%
“…Widbiller et al. (2023) found that LAI activation of both NaOCl and EDTA led to pronounced surface disintegration of root canal dentine, which was higher than that of sonic (Eddy) or ultrasonic activation. Hancerliogullari et al.…”
Section: Other Relevant Aspects With Regard To Laimentioning
confidence: 99%
“…The biofilms were irrigated by means of a blunt-ended 0.40 mm gauge needle (Endo-Eze, Ultradent, South Jordan, UT, USA). A soft ultrasonic device (tip 15) was used at frequencies of 20–30 kHz at 1 mm from the apical foramen during the final minute of irrigation in each group [ 25 , 26 ]. The antimicrobial activity was evaluated on three treated apices per group (as previously described).…”
Section: Methodsmentioning
confidence: 99%